A rare case of mosaic Klinefelter syndrome in a 45-year-old man leading to successful live birth through ejaculated spermatozoa: a case report and literature review - Hossam Elzeiny; Hossam Elzeiny; Franca Agresta; John Stevens; David K. Gardner; David K. Gardner (Frontiers in Genetics, 2023)
Background: Men diagnosed with Klinefelter syndrome (KS) commonly exhibit non-obstructive azoospermia or rarely having sperm in their ejaculate, rendering them traditionally considered sterile prior to the introduction of intracytoplasmic sperm injection (ICSI). The presence of mosaic KS may mask the classical phenotype, resulting in underdiagnosis throughout their lifetime. Surgical sperm retrieval through Microdissection Testicular Sperm Extraction (Micro-TESE) combined with ICSI has become the gold standard approach, maximizing reproductive outcomes in these individuals. However, it is noteworthy that approximately 7% of men with KS may exhibit sperm in their ejaculate, providing an opportunity for them to achieve biological parenthood through ICSI.Case Presentation: In this report, we present an exceptional case of a 45-year-old man with Mosaic KS and severe oligozoospermia who successfully achieved pregnancy utilizing ICSI with freshly ejaculated sperm. Remarkably, this case represents the oldest recorded instance of a man with Klinefelter syndrome fathering his own biological child using sperm derived from fresh ejaculate.Conclusion: Although this case is exceedingly rare, it underscores the critical importance of exhausting all possibilities to facilitate biological parenthood in men with KS before considering alternative options such as sperm donation or adoption. By recognizing the potential for successful conception using ejaculated sperm in this population, we can provide individuals with mosaic KS the opportunity to fulfill their desire for biological offspring.